Sex differences in the relationship between prescription opioid misuse and gun and other weapon-carrying behaviors. (1st April 2021) - Pontes, Nancy M.H.; Pontes, Manuel
Highlights: Adjusted marginal predictions (percentages) estimated with data from the US 2017 Youth Risk Behavior Survey show that among high school students who misused prescription opioids, male students had a higher prevalence of gun carrying (male = 21.1%, female = 6.2%), weapon carrying (male = 45.0%, female = 17.5%), and weapon carrying at school (male = 13.4%, female = 6.4%). Absolute measures (risk differences), estimated as per STROBE guidelines, show that the effects of opioid misuse on weapon-carrying are significantly greater among male students: gun carrying (male = 15.8% female = 5.1%), weapon carrying (male = 24.5%, female = 12.1%), and weapon carrying at school (male = 9.5%, female = 5.4%). In contrast, relative measures (odds ratios or risk ratios) show that the effects of opioid misuse on gun and weapon carrying are smaller among male students than female students. Risk differences, stratified by sex, should be reported when researchers investigate risk factors for gun or weapon carrying, especially with large secondary data sets. Abstract: Background: Previous research shows that adolescent prescription opioid misuse is strongly associated with weapon carrying. Method: For this research, data from the nationally representative 2017 Youth Risk Behavior Survey were analyzed. Average marginal predictions were estimated for gun and weapon carrying as a function of prescription opioid misuse and sex. As per STROBE guidelines, additive interactions with risk differences—in addition to multiplicative interactions with odds ratios and risk ratios—were estimated to investigate sex disparities in the effects of prescription opioid misuse on gun and other weapon-carrying. Results: Male US high school students who misused prescription opioids had an especially high prevalence of gun and other weapon carrying. Additive interactions show significantly greater risk differences associated with prescription opioid misuse among male students compared to female students for gun carrying, weapon carrying, and weapon carrying at school. In contrast, multiplicative interactions show lower odds ratios and risk ratios among male students for these same weapon-carrying variables. Discussion: Prescription opioid misuse is a significantly greater risk factor for gun and other weapon carrying among male US high school students, which disproportionately increases the risk for violence perpetration, including suicide among these students. Researchers should follow STROBE guidelines and report additive interactions and risk differences separately by sex when investigating risk factors associated with gun and other weapon carrying.